Anticancer and antimicrobial activities of supernatant fermented with pediococcus pentosaceus LAB8 or lactobacillus plantarum LAB10 - Zabidi, Nur Najihah (2017)
Chemotherapy is one of the mainstay of treatments against CRC and infectious diseases. This approach, however, suffers from limitations which include development of side effects and drug resistance. Probiotics appear to be a safer option when compared to chemotherapy as they can reduce symptoms and improve tolerability and effectiveness of chemotherapy. As such, the present study was undertaken to assess the anticancer and antimicrobial potential of Pediococcus pentosaceus LAB8- and Lactobacillus plantarum LAB10-fermented supernatant. LAB8 and LAB10 are unique strains of Lactic Acid Bacteria (LAB) with probiotic characteristics isolated from local fermented food. For anticancer assay, HCTl 16 (human colorectal cancer) cells were treated with serial dilutions of LAB8- and LAB 10-fermented supernatant (0.1-4%) for 72 hours. The SRB assay was then performed to determine cell viability. 5-FU was included as positive control. For antimicrobial assay, Gram negative E. coli and Gram positive S. aureus were exposed to LAB8- and LAB10-fermented supernatant (3.125-50%) overnight. Minimum inhibitory concentration (MIC) was determined by observing for the lowest concentration whereby visible growth of pathogens was inhibited. Ampicillin was included as positive control. The present results showed that at the highest tested concentration, 4%, LAB8- and LAB 10- fermented supernatant inhibited cell viability by 16% and 42%, respectively. LAB8- fermented supernatant yielded equal potency (MIC=25%) against S. aureus and E. coli. LAB 10-fermented supernatant, on the other hand, was more selective towards E. coli (MIC=12.5%) than S. aureus (MIC=25%).